Problematyka tożsamości w dyskursach dotyczących płci = The Identity Issue in Discourses Regarding Gender - Rejter, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is dedicated to the identity issue in academic discourses regarding gender. The chosen examples of this kind of discourse represent few thematic fields, as feminism, gender studies, queer studies and men`s studies.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie